Students’ Language Attitudes Towards English and Its Correlation with Students’ Speaking Skills - Putra, Pande Agus Putu Dharma; Adnyani, Ni Luh Putu Sri; Putra, I Nyoman Adi Jaya (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the students’ language attitude towards English and its correlation with students speaking skills of tenth-grade senior high school students in Bangli, Indonesia. Seventy-two tenth-grade students from one public school in Bangli, Indonesia, participated in this research. In collecting the data, the students answered a language attitude questionnaire adapted from Li & Wei (2022) and Siringo-ringo et al. (2023) for language attitude data and took a speaking performance test with the rubric adopted from O’Malley & and Pierce (1996). Descriptive statistics and Pearson Product Moment Correlation were used to determine the students’ language attitude levels and its correlation towards students speaking skills. The result from this study shows that the students’ language attitudes are positive in cognitive and affective aspects and fair in conative aspects. The correlational analysis results show a moderate and significant correlation between students’ language attitudes and speaking skills. (r = .517, p = .000). This result indicates that students’ language attitude still contributes enough to influencing students’ speaking skills. Keywords: language attitudes; speaking skills, correlational study